Mitochondrial ATP production is impaired in neural stem/progenitor cells derived from olfactory neuroepithelium of patients with schizophrenia. (13th April 2021) - Idotta, C.; Tibaldi, E.; Favaretto, N.; Pagano, M.; Peruzzo, R.; Pigato, G.; Cazzador, D.; Meneguzzo, P.; Solmi, M.; Leanza, L.; Favaro, A.; Brunati, A.M.; et al.
Abstract : Introduction: Neural stem/progenitor cells derived from olfactory neuroepithelium (hereafter OE-NS/PCs) are emerging as a viable proxy and a valuable tool for translational studies on severe mental illnesses (SMI). In this respect, the use of OE-NS/PCs as a surrogate cellular model of schizophrenia (SZ) has enabled insights into cell signaling and cell cycle dynamics in this disease. Objectives: We explored whether mitochondrial dysfunction, which has been already associated with SZ, may have a role in the altered proliferation pattern previously observed in OE-NS/PCs of SZ patients. Methods: OE-NS/PCs were collected from 20 patients and 20 healthy controls (Hcs) by nasal brushing, cultured in proper medium and expanded. Fresh OE-NS/PCs at passage 3 of both groups underwent BrdU proliferation assays or were frozen for later use. Mitochondrial ATP production was measured in both fresh and thawed OE-NS/PCs by using the ATPlite Luminescence Assay kit. Results: Fresh OE-NS/PCs of patients grew at a higher rate than those of HCs (M-W U=0; p<0.001), whereas the proliferation of thawed OE-NS/PCs of both groups exhibited an opposed pattern (at passage 6, p=0.002). Mitochondrial ATP production was significantly lower in OE-NS/PCs of patients than in those of HCs (M-W U=0; p=0.02), regardless of freeze-thaw conditions (M-W U=6; p=0.77). Conclusions: Mitochondrial ATP production is negatively affected in OE-NS/PCs of SZ patients as compared to those of HCs. This evidence does not differ in fresh OE-NS/PCs and OE-NS/PCs undergoing freeze-thaw cycles, which instead perturb the proliferation pattern of SZ OE-NS/PCs.